The influence of financial literacy of Economics Faculty students at Simalungun University on the use of e-money - Mahaitin H Sinaga; Yesni Riana Damanik; Yoan Hendrawan Junpridan Saragih (Trigin Publisher, 2023)
Participants in this study totaled 54,127 customers who made direct purchases of tofu walik Siantar on Jalan Kartini Pematangsiantar between January 20 and April 29, 2023, regardless of gender. Multiple linear regression is an analytical technique that was initially validated and tested for reliability. The findings of this study indicate that word of mouth influences purchasing decisions in a favorable and substantial way. This implies that the likelihood of making a purchase will increase with an increase in word of mouth. Total income has a favorable and substantial impact on purchasing decisions. This implies that purchasing choices will increase as income levels rise. Product quality has a positive and considerable impact on price.